2013
DOI: 10.18869/acadpub.3dj.1.2.1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Comparison of Conventional Film and Direct Digital Radiography in Proximal Caries Detection

Abstract: Introduction: Various systems for intraoral digital radiography have been available as an alternative to film-based radiography. In consideration of several advantages of digital radiography such as less patient absorbed dose, manipulation of image quality and elimination of processing, it has been extensively used in different fields of dentistry in recent years. The purpose of this study was comparison of conventional film and digital radiography in the proximal caries diagnosis. Materials and Methods: In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Castro et al 27 compared the diagnostic accuracy of Ekstaspeed Plus films and a direct digital system (Schick CMOS-APS sensor, Sirona) for the detection of approximal caries and found that both had poor performance in the detection of enamel lesions. Mohtavipour et al 28 compared an intraoral digital system (RVG, Trophy Radiologie, Paris, France) with F-speed films in the diagnosis of approximal caries and reported that for both modalities, the Az values were lower in caries restricted to enamel and enamel-dentin junction. Abesi et al 18 compared three intraoral modalities, namely E-speed films, PSP Digora PCT (Soredex) and CCD Dixi3 (Planmeca, Helsinki, Finland) in a study using noncavitated approximal surfaces of extracted posterior teeth and found higher sensitivity for films compared to digital systems for the detection of enamel caries, and similar sensitivity for both modalities for dentine caries.…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al 27 compared the diagnostic accuracy of Ekstaspeed Plus films and a direct digital system (Schick CMOS-APS sensor, Sirona) for the detection of approximal caries and found that both had poor performance in the detection of enamel lesions. Mohtavipour et al 28 compared an intraoral digital system (RVG, Trophy Radiologie, Paris, France) with F-speed films in the diagnosis of approximal caries and reported that for both modalities, the Az values were lower in caries restricted to enamel and enamel-dentin junction. Abesi et al 18 compared three intraoral modalities, namely E-speed films, PSP Digora PCT (Soredex) and CCD Dixi3 (Planmeca, Helsinki, Finland) in a study using noncavitated approximal surfaces of extracted posterior teeth and found higher sensitivity for films compared to digital systems for the detection of enamel caries, and similar sensitivity for both modalities for dentine caries.…”
Section: Discussionmentioning
confidence: 99%
“…Para el presente estudio la muestra fue la misma que la población. La muestra estuvo constituida por una base de datos de los diagnósticos radiológicos de 108 piezas dentales (50 molares y 58 premolares, con 106 superfi cies mesiales y 100 distales) siguiendo el mínimo muestral de 100 especímenes como en el caso de Mohtavipour (7), consta del diagnóstico radiológico de caries dental usando la técnica de aleta de mordida con radiografía convencional y técnica digital CCD (Charge Coupled Device). Los datos fueron proporcionados por el Departamento Académico de Medicina y Cirugía Bucomaxilofacial de la UPCH-FE (Universidad Peruana Cayetano Heredia -Facultad de Estomatología).…”
Section: Materials Y Métodosunclassified